Efficiency improvement of LDO ouput based linear regulator with supercapacitor energy recovery - a versatile new technique with an example of a 5v to 1.5 v version - Saiful Riza, Zainul Abidin (2011)
Supercapacitors are used in various industrial applications and the supercapacitors technology is gradually progressing into a mature state. Common applications of supercapacitors are in electric vehicles, hybrid electric vehicles, uninterruptible power supply (UPS) and in portable devices such as cellular phones and laptops. The capacitance values range from fractional Farads to few thousand Farads and their continuos DC voltage ratings are from 2V to 6V. At University of Waikato, a team works on using supercapacitors for improving the efficiency of linear voltage regulators. In particular, this patented technique aims at combining off the shelfs LDO ICs and a supercapacitor array for improving end to end efficiency of linear regulator. My work is aimed at developing the theoretical background and designing prototype circuitry for a voltage regulator for the case of unregulated input supply is more than 3 times of the minimum input voltage requirement of the LDO which is applicable for a 5V to 1.5V regulator. Experimental results are indicated with future suggestions for improvement.